Career Adaptability: The Key to Tackling Workplace Trauma at Scale - Hilder, Ian (International Journal of Advanced Corporate Learning (iJAC), 2021)
Over the last 12 months we have witnessed an acceleration of change within the traditional workplace. Digital disruption has only been exacerbated by Covid-19, displacement is rife, and the skills gap is widening exponentially. This report explores the concept of career adaptability, it’s origin and development but also how it can form the backbone of the response to overcoming workplace trauma. Exploring a ground-breaking, human centered response that will enable mentoring and employment support, at scale.